Territories of Equivalence - Clare Louise Lyster (Footprint)
The production regimes of every era do not remain in the factory but permeate every aspect of a society including its architecture and design culture. Mechanisation transformed space, in particular the household into an efficient machine, with industrial components and standardised dimensions (from the bathtub to the streamlined kitchen), while military manufacturing efficiencies and emerging technologies allowed consumer goods (from TV sets to Tupperware) to fill the middle class suburban home in the post-war era.